USULAN PERBAIKAN LAYOUT LANTAI PRODUKSI PT XYZ MENGGUNAKAN METODE ALGORITMA BLOCPLAN DAN ALGORITMA CORELAP - Tiaradia Ihsan; Rendiyatna Ferdian; Asep Anwar (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
PT XYZ is a company that engaged in the footwear manufacturing industry. In the production process, one of tool that required is cutting dies to form the desired designs or patterns. The production process that uses cutting dies is carried out in the moldshop section. Cutting dies are made from sheet plates that are cut to size, then processed to form a pattern or design that will be used in the main production section. Several departments were placed not in accordance with the production process flow, causing delays in the delivery of cutting dies. This also causes longer material handling time and there is irregular material flow such as cross material flow and alternating flow which also results in queuing processes. For this problem, it is necessary to design a layout to produce a shorter total distance and better production flow using the BLOCPLAN Algorithm and CORELAP Algorithm methods. From the design results, the proposed layout of the BLOCPLAN Algorithm was obtained which was able to produce a total distance of 2385.5 meters per day, whereas if using the CORELAP Algorithm it was 1514.63 meters per day. Therefore, it is recommended to use the layout from the CORELAP Algorithm calculation so that it can produce an efficiency of 20.60%.